Construction of chelation structure between Ca2+ and starch via reactive extrusion for improving the performances of thermoplastic starch. (3rd May 2018) - Zhang, Shuidong; Lin, Zesheng; Jiang, Guo; Wang, Junsheng; Wang, De-Yi
Abstract: A novel strategy was developed for the fabrication of thermoplastic starch with improved thermal and mechanical properties via chelating between starch and calcium gluconate (CG). Herein, the chelation structure between Ca 2+ and hydrogen group in starch was constructed via reactive extrusion. CG (5–20 wt% based on starch) was added to the mixture (corn starch (CS) and glycerol (70:30 wt%)), then the mixtures were extruded by twin-screws extrusion to fabricate thermoplastic CS/CG (TPS-CG). FT-IR and XPS test were employed to confirm the chelation structure of CS/CG. TGA and TG-FTIR results demonstrated that chelation structure improved the thermal stability of CS/CGs, while reduced the amount of toxic volatile gas from the CS decomposition. The results of DMA, mechanical and rheological tests for TPS-CGs revealed that all the data increased when CG content ranged from 5% to 20%. The maximal increase in glass-transition temperature, notched impact and tensile strength, melt viscosity of TPS-CGs was 20 °C, 52.4%, 44.2% and 360%, respectively. The mechanism for these improvements and their variations by CGs content were attributed to improving the entanglement of starch molecular chain and the stiffness of TPS-CGs via the chelation structure. The study provided a convenient solution for TPS fabrication with satisfied properties. Graphical abstract: Image 1